The potential therapeutic role of curcumin in osteoporosis treatment: based on multiple signaling pathways - Wang, Keyu (Frontiers in Pharmacology, 2024)
Osteoporosis is a common chronic metabolic bone disease caused by disturbances in normal bone metabolism and an imbalance between osteoblasts and osteoclasts.Osteoporosis is characterized by a decrease in bone mass and bone density, leading to increased bone fragility. Osteoporosis is usually treated with medications and surgical methods, but these methods often produce certain side effects. Therefore, the use of traditional herbal ingredients for the treatment of osteoporosis has become a focus of attention and a hot topic in recent years. Curcumin, widely distributed among herbs such as turmeric, tulip, and curcuma longa, contains phenolic, terpenoid, and flavonoid components. Modern pharmacological studies have confirmed that curcumin has a variety of functions including antioxidant and anti-inflammatory properties. In addition, curcumin positively regulates the differentiation and promotes the proliferation of osteoblasts, which play a crucial role in bone formation. Multiple studies have shown that curcumin is effective in the treatment of osteoporosis as it interacts with a variety of signaling pathway targets, thereby interfering with the formation of osteoblasts and osteoclasts and regulating the development of osteoporosis. This review summarized the key signaling pathways and their mechanisms of action of curcumin in the prevention and treatment of osteoporosis and analyzed their characteristics and their relationship with osteoporosis and curcumin. This not only proves the medicinal value of curcumin as a traditional herbal ingredient but also further elucidates the molecular mechanism of curcumin's anti-osteoporosis effect, providing new perspectives for the prevention and treatment of osteoporosis through multiple pathways.